Pengaruh Yoga Terhadap Kontrol Asma - Liqmayanti, Novi, Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2014)
Background: Asthma is a serious public health problem in many countries around the world. people with asthma will experience muscle spasms that can cause shortness of breath, difficulty in expiration, decreased lung capacity and physical condition will be weakened. Management of asthma guidelines aiming for a better quality of life with controlled asthma. Yoga is a physical and mental training methods for all the ages. Yoga will give relaxation to the body, blood circulation, breathing control. Yoga is very good for people with asthma and bronchitis. Objective: This study aimed to determine the effect of yoga on asthma control. Methods: This study is the use of quasi-experimental research, using the method of single-case approach research with pre and post test. Sampling using the total sample. Measuring the level of asthma control using the Asthma Control Test (ACT). Results: Test statistic using the Wilcoxon test and the obtained results mean p = 0.042 p <0.05, it is concluded that there is a difference between before and after treatment. Conclusion: There is the effect of yoga on asthma control. Seen from differences in questionnaire scores Asthma Control Test (ACT) before or after treatment